Meningkatkan Efektivitas Belajar Lempar Cakram Dengan Menggunakan Modifikasi Piring Plastik - Mistar Lumbantoruan (JURNAL GLOBAL EDUKASI, 2021)
Abstract: The aim of this research is to find out to what extent the plastic plate modification media can increase the effectiveness of learning to throw discs for fifth grade students of SD Negeri 12 Pintusona, Pangururan sub-district, Samosir district. This research was conducted at SD Negeri 12 Pintusona, Pangururan district, Samosir district, North Sumatra province. The subjects of this study were students in grade V. The research data were obtained from the results of student performance tests in throwing discs with a modified plastic plate media approach, which included: the preparation stage, the movement stage, and the final stage of the movement. Based on the results of the research that has been carried out, it can be concluded that learning to throw discs through the modification of plastic plate media in class V SD Negeri 12 Pintusona, Pangururan sub-district, Samosir district, can increase in three face-to-face sessions. Keywords: disc; plastic plate Abstrak: Tujuan yang ingin dicapai dalam penelitian ini adalah untuk mengetahui sejauhmana media modifikasi piring plastik bisa meningkatkan efektivitas belajar lempar cakram siswa kelas V SD Negeri 12 Pintusona kecamatan Pangururan kabupaten Samosir. Penelitian ini dilakukan di SD Negeri 12 Pintusona kecamtan Pangururan kabupaten Samosir provinsi Sumatera Utara. Subjek penelitian ini adalah siswa kelas V. Data penelitian diperoleh dari hasil tes unjuk kerja siswa dalam melakukan lempar cakram dengan pendekatan modifikasi media piring plastik, yang meliputi: tahap persiapan, tahap gerakan, dan tahap akhir gerakan. Berdasarkan hasil penelitian yang telah dilaksanakan, dapat disimpulkan bahwa pembelajaran lempar cakram melalui modifikasi media piring plastik di kelas V SD Negeri 12 Pintusona kecamatan Pangururan kabupaten Samosir dapat meningkat dalam tiga tatap muka. Kata Kunci: cakram; piring plastik